Shear thickening fluids and their applications - Minghai Wei; Kun Lin; Li Sun (Materials & Design, 2022)
Shear thickening fluids (STFs) are a new type of nanosuspension, which are formed by dispersing micro and nanoparticles in a dispersant. STFs are easily deformed under the action of a low shear rate. However, they instantly transform into a hard solid-like state at a high shear rate. After the removal of the impact force, STFs revert to their original liquid state. During this process, STFs absorb a significant amount of impact energy. Hence, they can be employed as a buffer and for vibration reduction. In this study, a comprehensive review of existing literature on STFs is presented. First, the basic properties, classification, and rheological mechanism evolution of STFs are discussed. The factors influencing the shear thickening behavior of these fluids are then reviewed. Subsequently, several computational models of the STF are discussed because the underlying mechanism of STF is still unclear, and to date, there is a paucity of good computational models. Finally, the research progress of composites based on STF in the fields of stab and spike resistance and low- and high-velocity impacts, and the use of STF as a new energy dissipation medium in the fields of explosion resistance, vibration control, adaptive structure, and industrial polishing are summarized.